2018
DOI: 10.1108/cfri-06-2017-0106
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cash flow volatility on firm leverage and debt maturity structure: evidence from China

Abstract: Purpose The purpose of this paper is to investigate the influence of cash flow volatility on firm’s leverage levels. It also analyzes how cash flow volatility influences the debt maturity structure for the Chinese listed firms. Design/methodology/approach The authors construct the measure for cash flow variability as five-year rolling standard deviation of the cash flow from operations. The authors use generalized linear model approach to determine the effect of volatility on leverage. In addition, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 66 publications
3
28
0
15
Order By: Relevance
“…This result is also not in line with Dess ı and Robertson ( 2003), who find that firms with more volatile cash flow are likely to have more debt in their capital structure. However, our results are consistent with Memon et al (2018) and Keefe and Yaghoubi (2016), who find that high cash flow of volatile firms tends to reduce debt but continues the use of non-financial liabilities. Our results do support the pecking order theory, that firms with more available funds use fewer external sources of financing than other comparable firms (Mateev et al, 2013).…”
Section: Determinants Of Capital Structuresupporting
confidence: 91%
See 1 more Smart Citation
“…This result is also not in line with Dess ı and Robertson ( 2003), who find that firms with more volatile cash flow are likely to have more debt in their capital structure. However, our results are consistent with Memon et al (2018) and Keefe and Yaghoubi (2016), who find that high cash flow of volatile firms tends to reduce debt but continues the use of non-financial liabilities. Our results do support the pecking order theory, that firms with more available funds use fewer external sources of financing than other comparable firms (Mateev et al, 2013).…”
Section: Determinants Of Capital Structuresupporting
confidence: 91%
“…However, Mateev et al (2013) find that if firms have more available internal funds, then they will take fewer external funds, which supports pecking order theory. Furthermore, Memon et al (2018) indicate that firms which face higher cash flow volatility tend to choose debt with shorter maturity.…”
Section: Earning Volatilitymentioning
confidence: 99%
“…Leverage is the degree to which an organization is financed with borrowed money [32,43]. These factors are traditionally used to explain debt structure variations.…”
Section: Leveragementioning
confidence: 99%
“…Meanwhile, the relations between LEV and CFO, Tobin's Q, and MBR are rejected. These contradict Memon et al (2018), who found negative impact of LEV towards CFO, Tobin's Q, and MBR.…”
Section: Hypotheses Testing and Discussionmentioning
confidence: 66%